A comparative literary study of Daniel and Revelation shaping the end - Sims, James H. (Lewiston, NY [u.a.] Mellen Biblical Press, 1995)
This study shows similarities in Daniel's and Revelation's structural combination of genres (narrative vision, prophecy-apocalyptic, epistle-vision), explores similarities in their characterization of the central characters and of some divine figures, and analyzes the effect on structure of the distinctive outlook of each author: horizontally through history in Daniel and vertically upward in imminent expectation in John's vision. Part I deals with the genre, chronology and historicity of Daniel, and suggests a new approach to the problems of "mixed genre" and "historical errors," showing the literary unity binding Daniel's narratives and visions together. Part II discusses the prophetic, apocalyptic, and epistolary characteristics of the Book of Revelation and provides a literary analysis of the whole as a unified work of art. Part III analyzes Daniel and Revelation intertextually, focusing particularly on previously unnoted similarities in structural and thematic unifying features of the works. There is also a consideration of the influence of each book on English literature.
Includes bibliographical references and indexes
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bibel; Bibel; Apokalyptik